Effect of short duration high temperature stress on bambara groundnut (Vigna subterranea (L.) Verdc.) plant reproduction - Dhanaraj, Bhavya (2018)
Agricultural production is at the mercy of uncertainties driven by climate change, as a result of this most of the major and minor crops are under threat of crop failure due to the severity of its effects on ‘crop fertility’. Plant reproduction is regarded as highly sensitive to such climatic changes, especially under high temperatures stress. Therefore, a key strategy to adapt to ever-increasing global temperature is by improvement and promotion of underutilised crops, one such future crop and the main focus of our research is bambara groundnut (Vigna subterranea [L] Verdc.). The present research was aimed at investigating the effect of temperature stress on plant reproduction, however, there is very limited data on how bambara groundnut genotypes differ in their response to temperature stress with respect to plant reproduction. Therefore, the focus of this research was a systematic study to establish firstly a guide to the reproductive development and, to quantify the impact of high temperature stress on floral development, pollination to fertilization and pod set in bambara groundnut.